Teaching Mathematics to Blind Students in Ethiopia - Milki, Tsegaye Gerba; Hailu, Belay Hagos; Malle, Abebe Yehualawork (International Journal of Global Community, 2025)
This study aimed at assessing Ethiopian primary school Mathematics teachers’ knowledge on teaching mathematics to blind students. The study employed a Descriptive survey design. A total of four hundred twenty-five sample participants were chosen from Addis Ababa, Oromia, Sidama, and South Nation, Nationalities and Peoples’ Region Primary school mathematics teachers using proportionate random sampling technique. Data was collected through structured questionnaire with 24 items and were analyzed using the Statistical Package for Social Science (SPSS). Descriptive and inferential statistics were used to describe the results. Results indicated that 84.7% and 92.11% of Ethiopian primary school mathematics teachers lacked technological and pedagogical knowledge respectively for teaching mathematics to blind students. Statistically significant mean difference was observed between the expected mean (1) and the calculated mean (0.000) at 95%confidence interval (P=0.05). However, no statistically significant mean difference were observed between age groups, sex, qualifications, teaching experiences and subject of specialization in teaching mathematics to blind students. The finding implied that the Ethiopian teacher education curriculum and training approaches lacked the Technological component of the TPCK model. The re-visiting of the pre-service mathematics teacher education and the deployment of intensive TPCK on-job training for mathematics teachers were recommended in order to employ the widely accepted inclusion principles in response to the right of blind students’ participation and achievement in socio-economic endeavors.